The EFL Teachers Eclectic Teaching Strategies in Teaching Speaking at the Tenth Grade of SMA Islam Athirah Bone - Andi Masriadi Andi Masriadi Tarmin; Kisman Salija; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research is aimed to describe the strategies utilized by the Englsih teacher in teaching speaking to the tenth grade students of SMA Islam Negeri Athirah Bone. This study utilizes a qualitative research design focusing on interviews. The study was conducted with one English teacher as the research subject. The findings of the research indicates that the teacher utilized a variety of strategies, in this case, role-play, dialogue, group discussion, modeling use of media or technology, storytelling, peer teaching, simulation, interactive games, presentations, language games, think-pair-share, task-based learning, question and answer sessions, improvisation activities, use of authentic materials, and error correction and feedback sessions. The result also shows that integrating students interests and using a diverse range of strategies positively impact their speaking abilities.